THE EPIDEMIOLOGY OF PLASTIC SURGERY CASES IN A TERTIARY GENERAL HOSPITAL IN SURABAYA, INDONESIA - Dwika Intania Riano; Lavonia Berlina Adzalika; Indri Lakhsmi Putri; Rachmaniar Pramanasari (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: Medical data registries play a crucial role in improving medical knowledge and enhancing patient care. Burn injuries, microtia, and orofacial clefts were identified as the most common occurrences among the patients The demographic patterns observed provide valuable insights into the patient population seeking plastic surgery services. Abstract: Introduction: Medical data registries are useful databases with well-defined data collection mechanisms. A well-designed and implemented registry can give surgeons a wealth of data for research and quality improvement efforts. The aim is describe the epidemiology of plastic surgery cases in a tertiary general hospital in Surabaya, Indonesia. Methods: A retrospective assessment of patients' medical records from 2016 to 2019 at Plastic Reconstructive and Aesthetic Surgery Unit, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia was conducted. A variety of factors were recorded and evaluated, including the patients' age, gender, diagnosis, and year. Results: We found that among 736 individuals' medical records during a four-year period, burn injuries (17.4%), microtia (11.7%), and orofacial clefts (11.5%) were the most prevalent occurrences. The majority of patients with burn injuries (31.3%), those with microtia (39.5%), those with cleft lip and palate (33%), and those with microtia (between the ages of 15 and 24) were all between the ages of 45 and 64. Patients who were men (52.6%) outnumbered those who were women (47.4%). This data indicates that there were more patients in 2019 than in previous years (397.%). Conclusion: The analysis of plastic surgery cases revealed a steady increase in the number of cases each year. Burns accounted for the biggest percentage of patient requests for care (17.4%). The majority of patients were male, and 21.9% of them were between the ages of 15 and 24 who were seeking care most frequently.